BIOLOGICAL FERTILIZER AS A SOURCE OF ENVIRONMENTAL POLLUTION - Sherkuziyeva G. F. (European Journal of Interdisciplinary Research and Development, 2024)
One of the current global problems is the growing population and providing them with ecologically clean food products. This will further increase the demand for agricultural products. The new biological fertilizer intended to be used in agriculture pollutes the environment, especially the air, open water bodies and soil, and at the same time, it can have a negative impact on human and animal life. Because biofertilizers also affect agricultural products, the production of safe products is important for public health. After application of the drug, it was determined that the amount of residue was retained in the plants for 3-8 days, and this amount depended on the method of application of the drug. Especially in potatoes, the most residual amount for 8 daysIt was determined in the amount of 2.9 mg/kg.